Clinical Trials in Ovarian Cancer - Walsh, Christine (Rutgers University Press, 2021)
The first book to collect and synthesize cutting-edge research findings on the treatment of gynecological malignancies into one easy-to-use reference, Clinical Trials in Ovarian Cancer provides physicians with an invaluable resource. Gynecologic oncologist Christine S. Walsh systematically outlines each of the seminal Phase III trials that have shaped the treatment of ovarian cancers, detailing the rationale for the trial, the patient population studied, treatment delivery methods, efficacy, toxicity, and trial conclusions.